2011
DOI: 10.1186/1471-2253-11-7
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative cognitive deficit after cardiopulmonary bypass with preserved cerebral oxygenation: a prospective observational pilot study

Abstract: BackgroundNeurologic deficits after cardiac surgery are common complications. Aim of this prospective observational pilot study was to investigate the incidence of postoperative cognitive deficit (POCD) after cardiac surgery, provided that relevant decrease of cerebral oxygen saturation (cSO2) is avoided during cardiopulmonary bypass.MethodscSO2 was measured by near infrared spectroscopy in 35 patients during cardiopulmonary bypass. cSO2 was kept above 80% of baseline and above 55% during anesthesia including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 19 publications
1
14
1
1
Order By: Relevance
“…Fudickar et al [ 38 ] use minimum ScO 2 to predict the occurrence of POCD, but only found week predictive performance (AUC = 0.61), while we found that ScO 2 after multiple influential factors had better discriminatory power for POCD. ScO 2 less than 50 % or decrease 20 % from baseline during carotid endarterectomy indicated focal cerebral ischemia [ 39 ], and were commonly regarded as safe limits of ScO 2 and chosen as the low limits in the present study.…”
Section: Discussioncontrasting
confidence: 69%
“…Fudickar et al [ 38 ] use minimum ScO 2 to predict the occurrence of POCD, but only found week predictive performance (AUC = 0.61), while we found that ScO 2 after multiple influential factors had better discriminatory power for POCD. ScO 2 less than 50 % or decrease 20 % from baseline during carotid endarterectomy indicated focal cerebral ischemia [ 39 ], and were commonly regarded as safe limits of ScO 2 and chosen as the low limits in the present study.…”
Section: Discussioncontrasting
confidence: 69%
“…It has been reported that a 5% to 15% decrement in rScO 2 from baseline on the side ipsilateral to carotid cross-clamping has a 44% to 100% sensitivity and 44% to 100% specificity for predicting changes in CBF velocity as measured by transcranial Doppler, EEG slowing, or changes in SSEPs. [5155] These studies have limitations such as small sample size. One of the largest studies to date, which involved almost 600 patients who underwent CEA under general anesthesia, found that a 11.7% decrease from baseline in rScO 2 had a sensitivity of 75% and a specificity of 77% for detecting neurological complications [66].…”
Section: Carotid Artery Surgerymentioning
confidence: 99%
“…Sample size calculation was estimated in previous studies investigating POCD by Hudetz et al [21] and by our own group [17], [22]. We assumed that the incidence of POCD could be reduced from 30% in the control group to 20% in the RIPC group, and we added 50% of the patients enrolled in the study.…”
Section: Introductionmentioning
confidence: 99%